Myocardial fibrosis in Type 2 Diabetes is associated with functional and metabolomic parameters. (15th September 2022) - Dennis, Mark; Howpage, Sashie; McGill, Margaret; Dutta, Shashwati; Koay, Yen; Nguyen-Lal, Lisa; Lal, Sean; Wu, Ted; Ugander, Martin; Wang, Alexandra; Munoz, Phillip A.; Wong, Jencia; et al.
Abstract: Aims: To identify biomarkers of cardiomyopathy in patients with type 2 diabetes mellitus (T2DM) using cardiovascular magnetic resonance (CMR) and to identify associations between functional status, metabolomic profile and myocardial fibrosis. Methods: In this prospective case control study, patients ( n  = 49) with T2DM without significant coronary artery disease, and matched controls ( n  = 18) underwent CMR, cardiopulmonary exercise testing, and plasma metabolomic analyses. Results: Patients with T2DM ( n  = 49, median [interquartile range] age 61 [56–63] years, 61% male, diabetes duration 11 [7–20] years), historical HbA1c 7.6% (60 mmol/mol) (6.9–8.6) and matched controls ( n  = 18) were examined. Study patients had increased myocardial extracellular volume (ECV) (26.9 [23.8–30.0] vs 23.4 [22.4–25.5) %, p  < 0.001). Increased ECV was associated with male sex ( p  = 0.04), time with T2DM ( p  = 0.02), reduced peak VO2 (R2 = 0.48, p  = 0.01), increased circulating choline ( p  = 0.002) and cysteamine (p = 0.002) both of which were also associated with reduced peak VO2 ( p  < 0.025 and 0.014 respectively). Conclusions: Patients with well-controlled T2DM without significant coronary disease exhibit focal and diffuse myocardial fibrosis and diffuse myocardial fibrosis is associated with reduced exercise tolerance and metabolites. Plasma metabolites may provide mechanistic insights into diffuse myocardial fibrosis, and cardiopulmonary fitness. Highlights: Patients with Type 2 Diabetes Mellitus have increased risk of adverse cardiovascular events independent of coronary disease A significant number of patients with Type 2 Diabetes have focal or diffuse myocardial fibrosis on CMR Diffuse fibrosis (raised ECV) is associated with reduced exercise capacity selected metabolites